Developing A Storybook as Supplementary Material for Junior High Schools Students Based on Kalimantan Legends - Rinbud Rinardi; Ikhsanudin Ikhsanudin; Regina Regina (International Journal of Learning and Instruction (IJLI), 2019)
The main purpose of this research is to develop a storybook for junior high school students based on Kalimantan Legends. The participant of this research were 60 students of junior high school, and an educational expert from Kabupaten Sambas. This research used the platform of design and development research proposed by Richey and Klein. The procedure used is the framework of Jolly and Bolitho, that consist of need analysis, material grid, first draft, evaluation, and final draft. The data of this research has been collected through questionnaires. There were five questionnaires employed in this research. The first questionnaire was given to the students to investigate the need of the students on reading materials based on Kalimantan Legends. The second questionnaire was employed to know the favorite legends of students. From the need analysis result, it can be concluded that students are interested in reading (68.30 %), they like to read stories (90 %). The students are interested to read their local stories (95 %), and they like the stories with adequate illustrations to help them understand the stories completely (70 %). On the other hand, they thought that the stories they have in their textbooks were not interesting (65%).